Macromol. Chem. Phys. 5/2015. Issue 5 (March 2015) - Liu, Lijia; Long, Qing; Aoki, Toshiki; Namikoshi, Takeshi; Abe, Yunosuke; Miyata, Mari; Teraguchi, Masahiro; Kaneko, Takashi; Wang, Yudan; Zhang, Chunhong
<x xml:space="preserve">Abstract</x> Back Cover: A one‐handed helical supramolecular polymer membrane of 1, 3, 5‐trisubstituted benzenes was successfully prepared via the quantitative photocyclic aromatization reaction of a cis‐cisoidal poly(chiral substituted acetylene) membrane. The resulting one‐handed supramolecular helicity of the resulting polymer membrane could be retained even after in situ removal of the chiral substituents in the membrane. Further details can be found in the article by L. Liu, * Q. Long, T. Aoki, * T. Namikoshi, Y. Abe, M. Miyata, M. Teraguchi, T. Kaneko, Y. Wang, and C. Zhang on page 530. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>